2021
DOI: 10.2147/imcrj.s305693
|View full text |Cite
|
Sign up to set email alerts
|

Novel Coronavirus (COVID-19)-Associated Guillain–Barre’ Syndrome: Case Report

Abstract: Though the novel corona virus (COVID-19) mostly affects the respiratory system, it can also result in several neurological complications. One of these is Guillain-Barré Syndrome (GBS) and which is rare and only reported from some parts of the world during this pandemic. Guillain-Barré syndrome (GBS) is an immune-mediated polyradiculoneuropathy. Patients can present with limb or cranial-nerves weakness, loss of deep tendon reflexes, sensory and dysautonomic symptoms. The main pathophysiology for the clinical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Eight patients died, two of them due to cardiac arrest, two developed multiple organ failure, one due to severe respiratory distress, one was hemodynamically unstable, one developed severe autonomic dysfunction, and the last one developed respiratory failure secondary to GBS [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight patients died, two of them due to cardiac arrest, two developed multiple organ failure, one due to severe respiratory distress, one was hemodynamically unstable, one developed severe autonomic dysfunction, and the last one developed respiratory failure secondary to GBS [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our review had some strengths. Firstly, the inclusion of 73 cases report [ 5 , 12 , 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 27 , 29 , 30 , 31 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , ...…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 virus-induced immune dysregulation is reinforced by the documented recent association between immune thrombocytopenic purpura (ITP) and COVID-19 [ 9 ]. Other forms of autoimmune disorders in association with COVID-19 infection, including development of lupus anticoagulants [ 10 ], autoimmune hemolytic anemia [ 11 ] and Guillain-Barre syndrome [ 12 ] are increasingly reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Vojdani and Kharrazian [ 99 ] discovered that 21 out of 50 human tissue antigens had moderate to high strength responses to SARS-CoV-2 antibody, suggesting an antigenic cross-reaction between the SARS-CoV-2 epitope and various human tissue antigens. This cross-reaction can result in high titers of autoantibodies, inducing Guillain–Barre syndrome [ 100 ], lupus, antiphospholipid syndrome, and ANCA-associated vasculitis [ 98 ]. Franke et al [ 101 ] found that high levels of antibodies were detected in patients’ cerebrospinal fluid.…”
Section: Immunotherapymentioning
confidence: 99%